Private Information and Intertemporal Job Assignments. - Prescott, Edward Simpson; Townsend, Robert M. (Review of Economic Studies, 2006)
This paper studies the assignment of people to projects over time in a model with private information. The combination of risk neutrality with incomplete contracts that restrict the ability of an agent to report on interim states is a force for long-term assignments. More generally, however, rotating agents can be valuable because it conceals information from agents, which mitigates incentive constraints. With complete contracts that communicate interim states, rotation allows for even more concealment possibilities and better-targeted incentives. Furthermore, it allows for the reporting of interim shocks at no cost to the principal. Properties of the production technology are also shown to matter. Substitutability of intertem-poral effort is a force for long-term assignments, while coordination with Nash equilibrium strategies is a force for job rotation. Reprinted by permission of the publisher.